IMPACT OF YOGA ON BMI AND STRESS LEVELS FOR MIDDLE-AGED GOVERNMENT EXECUTIVES (CAHIERS MAGELLANES-NS, 2024)
This study investigates the effects of a structured yoga program on Body Mass Index (BMI) and stress levels among middle-aged government executives. These individuals often face increased risks of obesity and stress due to the high demands and sedentary nature of their work. A 12-week randomized controlled trial was conducted with 40 participants, divided into an experimental group participating in yoga sessions and a control group maintaining their usual routine. Results demonstrated significant improvements in BMI and reductions in stress levels in the experimental group compared to the control group. These findings suggest that yoga can be an effective intervention for enhancing physical and mental well-being in this demographic.